Behavioral Risk Factors for Non-Communicable Diseases among Adult Population: A Cross Sectional Study from Urban Slums of Central Karnataka, India - Richa Garg; Shubha Davalagi (Medsci Publications, 2018)
Background: Non-communicable diseases, account for 53% of the deaths and 44% of Disability Adjusted Life Years in India. Although these chronic diseases are highly prevalent in urban areas, they are inadequately detected. Objectives: The objective of the study was to find out the prevalence of behavioral risk factors for non-communicable diseases among urban slum population. Materials and methods: A cross- sectional study was conducted using WHO STEPS approach questionnaire at urban field practice area of tertiary care teaching hospital, Davangere. The study for conducted for the duration of 3 months including 196 study participants. Results: Among study population, 37% used smoked tobacco products and 43% used smokeless tobacco products. 23% of the study population consumed alcohol occasionally with no female reported consuming alcohol in the study. 37% of the study participants add salt to the prepared food. 19% were diagnosed as hypertensives among which 18% were on treatment at the time of the study. 22.4% were diagnosed as diabetics among whom 21.9% were on treatment at the time of study. No female participants in the study ever underwent screening of cancer cervix. Conclusion: Promotion of healthy lifestyles at individual and community level is the need of modern time.